Effect of grinding process parameters on surface roughness of aluminium alloy 6061-T6 - Aziema, Mohamad Azizi (2008)
In manufacturing industry, surface quality of the material very important for certain applications such as in aerospace industry. There are demands for grinding manufacturers in aerospace industry to get good surface finish and tolerance requirements for aerospace components such as wings to reduce the friction and wear resistance. The grinding process is the most suitable process to obtain a very good surface finish and accuracy. The objectives of this research are to investigate and analyze the effects of grinding process parameters on surface roughness of aluminium alloy 6061-T6 (AA 6061-T6). The machining parameters used in this research are the depth of cut, number of passes and use of coolant. A full factorial experiment design was used as the approach for the design of experiment. It was found that the surface roughness of aluminium alloy 6061-T6 decreased when the number of passes increased. Oppositely, surface roughness increased when the depth of cut increased. Meanwhile the surface quality